A global compass for the great divergence: emissions vs. production centers of gravity 1820-2008 - Caspar Sauter; Jean-Marie Grether; Nicole A. Mathys (Center for Economic Studies and ifo Institute (CESifo), 2019)
We construct the world's centers of gravity for human population, GDP and CO2 emissions by taking the best out of five recognized data sources covering the last two centuries. On the basis of a novel distorsion-free representation of these centers of gravity, we find a radical Western shift of GDP and CO2 emissions centers in the 19th century, in sharp contrast with the stability of the demographic center of gravity. Both GDP and emissions trends are reversed in the first half of the 20th century, after World War I for CO2 emissions, after World War II for GDP. Since then, both centers are moving eastward at an accelerating speed. These patterns are perfectly consistent with the lead of Western countries starting the industrial revolution, the gradual replacement of coal by oil and gas as alternative sources of energy, and the progressive catch up of Asian countries in the recent past.
Keywords: Q56; Q59; 330; center of gravity; growth; CO2 emissions; GDP; population; great divergence